Царь Федор Иванович - Володихин Дмитрий Михайлович (Жизнь замечательных людей, 2011)
Экземпляры: Аб.,9ф.,10ф. (17.09.2012г.) / Инвентарный номер: 47043 / Цена: / Сис.шифр: 63.3(2)43 / Авт.знак: В68 / ББК: 63.3(2)43